Analysis of Wireless Tactical Networks (WTN) - Srivastava, Atul Ranjan (INFOCOMP Journal of Computer Science, 2019)
In the present paper the goal of the WTN program was to develop an adaptive networking capability that dramatically improved performance and reduced communication failures in complex communication networks. The past decades have witnessed advances in computing and communication technologies. Faster, smaller and more reliable devices enable communications with rapid, efficient information dissemination between mobile. Mobile ad hoc networks have several advantages over traditional wireless networks. These advantages are on demand setup, fault tolerance, node’s increased mobility, self-organizing connectivity, adaptive, scalable ad hoc network routing. Today’s tactical networks are a complex network centric system, where sensor systems, unmanned vehicle systems, and distributed systems of mobile units, transfer and analyze data while they are moving . Tactical wireless networks should provide reliable, survivable, secure and seamless communications capabilities to the tactical edge. A tactical wireless network often experiences connectivity problems for a variety of reasons including limited or no fixed network infrastructure, dynamically maneuvering units, challenging transmission conditions, and faulty network and collaboration schemes.